Intra-Articular Steroid Injections and their Associations with Superficial Surgical Site Infections and Nonunion Rates - Jenny Nguyen BSc; Kyra Robinson BS; Michelle M. Coleman MD, PhD (Foot & Ankle Orthopaedics)
Category: Ankle; Arthroscopy Introduction/Purpose: Many surgeons avoid performing intra-articular corticosteroid injection (IACI) in the immediate preoperative period due to concerns for an increased risk of postoperative complications such as superficial surgical infections [SSI]. Prior studies of patients undergoing total hip and total knee arthroplasties have demonstrated mixed findings regarding increased risk of SSI in patients receiving an IACI within 3 months. However, there is a paucity of research concerning post-surgical complications of foot and ankle patients following IACI. This study aims to examine the effects of preoperative IACI after foot and ankle joints on rates of SSI and nonunion. We hypothesized that there would be an increased rate of SSI and non-union for patients receiving injections 6 months before a fusion procedure compared to a non-fusion procedure. Methods: MarketScan database was queried for patients undergoing fusion and non-fusion procedures of the first metatarsophalangeal (MTP) and ankle joint between January 2009 through December 2022. Patients were included in the study cohort if there was a preceding IACI within 6 months of their procedure. Patients were separated based on whether their injection was within 1 month, 2-3 months, or 3-6 months before their procedure. The control group were patients who received an injection within 3-6 months before the procedure. ICD9/10 codes were used to identify patients who experienced an SSI or nonunion to calculate the prevalence postoperatively. Chi-square analyses were used to evaluate whether there was a significant difference in rates of infection and non-union among patients receiving corticosteroid injections 1 month, 2-3 months, or 3-6 months before their surgical procedure (α = 0.05). Results: Overall complication rates of SSI ranged from 3.42% to 12.65% with nonunion rates ranging from 0.34% to 24.10%. Patients who received a steroid injection 1 month, 2-3 months, or 3-6 months and then underwent subtalar arthrodesis had corresponding infection rates of 12.65%, 7.17%, 8.20%, which was the highest amongst the procedures studied. Nonunion was also most prevalent undergoing subtalar arthrodesis; rates of nonunion of having a surgery within 1 month, 2-3 months, or 3-6 months before an injection were 24.10%, 21.51%, 21.51%, which was highest amongst the procedures studied. Complication rates for each procedure studied are listed in Table 1. Chi-square analyses demonstrated that there was no significant difference in the number of patients with a post-operative SSI or nonunion among the groups. Conclusion: In this study, there was no significant difference in rates of SSI and non-union between patients with pre-operative corticosteroid injections use in the groups studied. This was true in both simpler procedures such as cheilectomy and ankle arthroscopy as well as in procedures involving osteotomies and fusions (bunionectomy, MTP fusion, subtalar fusion, and ankle fusion). These results suggest that surgeons may consider corticosteroid injection, if needed, in the preoperative period without excessive increase in perioperative risks.